PARENTAL PERMISSIVENESS AND FAMILY FUNCTION TOWARDS UNWANTED PREGNANCIES OF ADOLESCENTS IN BORDER AREAS - Wahyuningsih, Lisa Dwi; Suwarni, Linda; Ridha, Abduh (Jurnal Ilmiah Ilmu Kesehatan: Wawasan Kesehatan, 2019)
ASFR in Sintang District in pregnancy 15-19 years is 9.85% highest in West Kalimantan.This because of free sex. Many factors that cause pregnancy in teenagers one of them is the permissiveness of parents and the application of family functions. The purpose of this study was to determine the description of parental permissiveness toward adolescent dating behavior, the application of family functions, and the incidence of unwanted pregnancy in adolescents in Sintang District. The type of research used was observational with a cross sectional approach. Research was carried out in the working area of Puskesmas in Sintang District. Data collection techniques using questionnaires. The population in this study were all pregnant women aged <20 years in the Sintang District Work Area obtained from the cohort. The study sample was 52 people. The results showed that the permissiveness of parents to the dating behavior of adolescents with unwanted pregnancies was partially permissive, namely (61.5%). Permissive parental statements showed parents entrusting children to courtship 96.2%, parents leaving a relationship with boyfriend 86.5%, parents freeing courtship 69.2%, parents considered courtship ordinary matters 96.2% and 36,5% does not support the function of families with unwanted pregnancies. The family function statement showed that there was a culture gathered on a certain day 84.6% tradition of drinking alcohol 82.7%. results of dating behavior of adolescents, adolescents (kissing) 96.2%, (necking) 38.5%, (petting) 34.6%, (intercourse) 57.7% and ever accessing pornographic media by 57.7%. And most of their feelings of being married <20 years are normal at 55.8% even though 25.0% feel sorry.